Hubungan Antara Perhatian Orang Tua Dengan Disiplin Belajar Siswa Kelas VIII Madrasah Tsanawiyah Negeri 2 Mojokerto pada Tahun Pelajaran 2019/2020 - Joko Widoyoko; Dian Triana; Abdul Rouf (Arsy : Jurnal Studi Islam, 2019)
Background of about problem opus this is family role Eroding in its function as sentral education is first and main by a variety the growth of technology, urbanization and complete lives. Meanwhile its aim for example: Want to know marks sense or not mark sense relationship among oldster attention with disciplined learned student. Its utility 1) To increase creativity and efficiency development in observational. 2) as contribution of thinkings in trouble education. 3) as information on society (oldster) that oldster attention as one of success tool of an education aim.4) Contribution collect thoughts to increase discipline quality study child. Observational type is correlation among two Variables (at liberty and overcharging) with outgrows this research sample as much 52 students (son and daughter). Data collecting source with Questionnaire method. Its reason is easy analysis and more on respondent one is wanted without marks sense respondent relationship influence with researcher. Its sampling type utilizes Stratified Proportional Random Sampling (of aught population have same chance as sample).Result a stop to this research points out To Mark Sense relationship that adequately signifikan among oldster attention with disciplined learned student brazes VIII . MTsN 2 Mojokerto schole Year 2019 / 2020, in mean 1) The greater oldster attention that is given on its daughter son, studyings disciplined excelsior it. 2) the greater oldster attention those are given on its daughter son, progressively contemns too disciplined its studying. Tipses 1) Ought to oldsters more increase attention on its daughter son. 2) Ought To students more increase its studying disciplines that good crescent. 3) Ought To on each good studying activity on the house and also at executed school seriously and heaving full discipline.